2017
DOI: 10.14453/aabfj.v11i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Quality, Board Gender Diversity and Corporate Dividend Policy: Evidence from Jordan

Abstract: This paper examines the impact of corporate governance quality and board gender diversity on the corporate dividend policy for a set of all non-financial companies listed on Amman Stock Exchange (ASE) during the period 2009-2015. The results documented that corporate governance quality and board gender diversity proxies have positive impact on corporate dividend policy. The results also showed that the women representation on the boards of non-financial companies in Jordan is considered low relative to other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 24 publications
1
13
1
Order By: Relevance
“…The results supported our hypothesis, as Asian emerging economies presented the negative impact of board gender diversity and family ownership on dividend announcements of firms. The findings of our research were contradictory to previous studies that were conducted in established economies that suggest that women on boards positively affect the dividend policy of firms (Nasrum 2013;van Essen et al 2015;Pucheta-Martínez et al 2016;Byoun et al 2016;Chen et al 2017;Al-Rahahleh 2017;Gyapong et al 2019). However, Robtus and Cox (1991); Rose (2007); Richard et al (2004); Attig et al (2016); Sanan (2019); Jonge (2014); and Liu et al (2013) have explained that it is not easy for women to emerge in firms.…”
Section: Discussioncontrasting
confidence: 99%
“…The results supported our hypothesis, as Asian emerging economies presented the negative impact of board gender diversity and family ownership on dividend announcements of firms. The findings of our research were contradictory to previous studies that were conducted in established economies that suggest that women on boards positively affect the dividend policy of firms (Nasrum 2013;van Essen et al 2015;Pucheta-Martínez et al 2016;Byoun et al 2016;Chen et al 2017;Al-Rahahleh 2017;Gyapong et al 2019). However, Robtus and Cox (1991); Rose (2007); Richard et al (2004); Attig et al (2016); Sanan (2019); Jonge (2014); and Liu et al (2013) have explained that it is not easy for women to emerge in firms.…”
Section: Discussioncontrasting
confidence: 99%
“…Further, as women are risk averse, diverse boards are likely to induce in more dividend payments in order to avoid agency conflict too. Our results are in line with the previous research which shows that gender diversity on board leads to high dividend payments (Al-Rahahleh, 2017;Pucheta-Martinez & Bel-Oms, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…There is currently a paucity of such research in developing countries. Limited prior studies which have been conducted in developing countries have concentrated on financial sectors such as banks (Khan, 2010;Bukair and Rahman, 2015;Kiliç et al, 2015) where the disclosure requirements are different than compared to non-financial sectors (Ahmed Haji, 2013;Al-Rahahleh, 2017). Other studies which have examined non-financial sectors in developing countries found mixed results.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study investigates all non-financial listed companies on the Amman Stock Exchange (ASE) for the period of 2006 to 2015. Financial sectors are excluded because their disclosure requirements are different to non-financial sectors (Ahmed Haji, 2013;Al-Rahahleh, 2017). The longitudinal data results in balanced panel data of 800 observations.…”
Section: Introductionmentioning
confidence: 99%